Contraceptive awareness and practices in women of urban India - Upadhye, Jayshree J.; Upadhye, Jayant V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: With the efforts from government and increase in the literacy of women, awareness about contraceptive methods is increased. The objective of the study was to analyse contraceptive awareness and practices in women and to find out the source of information and reason for non-use of contraception. Methods: In a cross-sectional study 400 women were interviewed from July to December 2016. Results: In our study, majority (43.5 %) of women were between 26-30 years of age followed by women between 22-25 years of age (26.5 %). 92.5% of women were aware of one or other method of contraception. But only 42.5% were practicing contraception. Maximum awareness was about tubectomy (90.5%) followed by CuT (87.5%), Condom 50%, O.C. pills 12.5%, Safe period 5% and injectables 2.5%. Most common method used in our study group was condom (20%) followed by tubectomy 12.5%, CuT 7.5%, O.C. Pills 1.5%, Injectable contraceptive and safe period 0.5% each. 37.5 % woman got information from radio or newspaper, 30 % from hospital doctor, 25 % from friends or relatives, 7.5 % had no information. 100% women were literate, 70% had education till high school, 30% were graduate or postgraduate. In our study, 52.5% had no reason for non-use of contraception.25% were not using due to myths or fears while 22.5% were not using due to family pressure. Conclusions: We concluded that awareness about contraceptive methods is quite high but acceptance is quite low. Condom is the most common method used.